Assessment of local government autonomy and governance: A case study in Nigeria - Anayochukwu, Grace Ifunanya; Ani, Vincent Anayochukwu; Nsah, Bernard (Goodwood Publishing, 2022)
Purpose: This paper critically examines opportunities and problems confronting the Nigerian local government system. To assess why the practice of complete local government autonomy and governance is difficult in Nigeria and suggest measures that may help improve the collaboration between the federal, state, and local government authorities in Nigeria. Research methodology: 300 questionnaires were administered to the staff of the Nkanu-West Local Government Area in Enugu State, and 276 were returned giving a response rate of 92 percent. The Marxist theory was adopted as the theoretical framework. Results: Results show that state interference in local affairs contributes to a lack of local government autonomy and governance, and the constitutional provisions portend intractable inter-government problems which make the local government a whipping child and less autonomous. Limitations: Nkanu-West local government is the only local government covered by the study. Contribution: The outcome of the study will be a contribution to the existing literature in the area of local government autonomy and governance.